Rousseau and the Problem of Human Relations - Warner, John M. (Penn State University Press, 2018)
Among Jean-Jacques Rousseau's chief preoccupations was the problem of self-interest implicit in all social relationships. A person with divided loyalties (i.e., to both himself and his cohorts) was, in Rousseau's thinking, a divided person. According to John Warner's Rousseau and the Problem of Human Relations, not only did Rousseau never solve this problem, he believed it was fundamentally unsolvable: social relationships could never restore wholeness to a self-interested human being. Warner traces his argument through the contours of Rousseau's thought on three distinct types of relationships-sexual love, friendship, and civil or political association. Warner concludes that none of these, whether examined individually or together, provides a satisfactory resolution to the problem of human dividedness located at the center of Rousseau's thinking.